KECEMASAN DALAM MEMPELAJARI BAHASA ASING PADA SISWA SMA DI TORAJA - Reynathal Beatrix; Rahmah Hastuti (Jurnal Psikologi Malahayati, 2022)
ABSTRACT: FOREIGN LANGUAGE LEARNING ANXIETY IN HIGH SCHOOL STUDENTS IN TORAJA Language is a tool of communication used by individuals to facilitate communication and express something. Therefore, language is an important material to learn, not only regional languages, but also foreign languages, especially for high school students in Indonesia. However, learning a foreign language can cause anxiety for students who think that foreign languages are difficult to learn. Therefore, this study aims to obtain an overview of anxiety in learning foreign languages in students of SMA Negeri X in Toraja. This research was conducted at SMA Negeri X in Toraja and 132 students participated in this study. The method used is descriptive quantitative through the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire to get a picture of students' anxiety when learning foreign languages at SMA X in Toraja. Data collection was carried out at SMA X in Toraja during October to December 2021. The results showed that the majority of students at SMA Negeri X in Toraja experienced moderate level of anxiety when learning English. The author also found that there was no difference between gender and anxiety in learning a foreign language. Based on research results, the majority   the student   High school   Neger   X   in   Toraja   experience   anxiety   level   intermediate   on   when   learn   language   English. Keywords: Anxiety, Foreign Language Learning, High School     Students Bahasa merupakan alat komunikasi yang digunakan oleh individu untuk memudahkan komunikasi serta mengekspresikasn sesuatu. Karenanya, bahasa merupakan materi yang penting untuk dipelajari, tidak hanya bahasa daerah, namun bahasa asing juga perlu dipelajari oleh individu, terutama siswa SMA di Indonesia. Namun, mempelajari bahasa asing dapat menimbulkan kecemasan bagi siswa yang menganggap bahwa bahasa asing itu sulit dipelajari. Karenanya, penelitian ini bertujuan untuk mendapatkan gambaran mengenai kecemasan dalam mempelajari bahasa asing pada siswa SMA Negeri X di Toraja. Penelitian ini dilakukan di SMA Negeri X di Toraja dan sebanyak 132 orang siswa yang berpartisipasi dalam penelitian ini. Metode yang digunakan adalah deskriptif kuantitatif melalui kuesioner Foreign Language Classroom Anxiety Scale (FLCAS)                 untuk mendapatkan gambaran mengenai kecemasan siswa pada saat mempelajari bahasa asing pada SMA X di Toraja. Pengambilan data dilaksanakan di SMA X di Toraja selama bulan Oktober hingga Desember 2021. Hasil penelitian menunjukkan bahwa mayoritas siswa SMA Neger X di Toraja mengalami kecemasan tingkat menengah pada saat mempelajari bahasa Inggris. Berdasarkan hasil penelitian, mayoritas siswa SMA Neger X di Toraja mengalami kecemasan tingkat menengah pada saat mempelajari bahasa Inggris. Kata Kunci: Kecemasan, Belajar Bahasa Asing, Siswa SMA